The contested community police officer: An ongoing conflict between different institutional logics - Terpstra, Jan (International journal of police science & management, 2019)
This paper concentrates on the ongoing conflict about the role and work of community police officers in the Netherlands. This conflict can be understood as a result of conflicting institutional logics. Although there are important differences between the community officers, there is the logic or perspective used by most of the community officers. This logic puts much emphasis on personal relations, trust-building, direct information, craftsmanship, tacit knowledge, involvement and discretion and experience. However, community officers have also been confronted with two other logics, with more emphasis on crime fighting and managerial control. In addition, there is also a third, more implicit logic, built upon a frame consisting of two opposing images of community officers. On the one hand, many of the current community officers are seen as old-fashioned and outdated. On the other hand, a more positive image of new community police officers is presented, called community officers 2.0 This can be seen as a way to create a new type of community police officers that is more in line with the managerial need for organizational control and with a more limited and instrumental view on community policing.